Nigella sativa Oil-loaded Ethanolic Vesicular Gel for Imiquimod-induced Plaque Psoriasis: Physicochemical Characterization, Rheological Studies, and In vivo Efficacy - Vihal, Samar; Pundir, Swati; Rathore, Charul; Lal, Uma Ranjan; Gupta, Gaurav; Singh, Sachin Kumar; Dua, Kamal; Chellappan, Dinesh Kumar; Negi, Poonam (Current Drug Delivery, 2025)
BackgroundThe therapeutic effect of NS oil in mild to moderate psoriasis is limited owing to low play load of thymoquinone (<15%w/w), irritation, dripping, low viscosity and thus, less contact time on the lesions.AimsThis study aimed at developing and characterizing the ethanolic vesicular hydrogel system of Nigella sativa (NS) oil (NS EV hydrogel) for the enhancement of anti-psoriatic activity.ObjectiveThe objective of this study was to develop NS EV hydrogel and evaluate its anti-psoriatic activity.MethodsThe identification and quantification of TQ content in different NS seed extracts and marketed oil were measured by an HPTLC method using n-hexane and ethyl acetate as solvent systems. Preparation of ethanolic vesicles (EVs) was performed by solvent injection method, while its anti-psoriatic activity was evaluated employing an Imiquad (IMQ)-induced plaque psoriasis animal model.ResultsA compact HPTLC band was obtained for TQ at an Rf value of 0.651. The calibration plot was linear in the range of 1-10 µg/spot, and the correlation coefficient of 0.990 was indicative of good linear dependence of peak area on concentration. From the different NS sources, the high TQ content was obtained in the marketed cold press oil, i.e., 1.45±0.08 mg/ml. Out of various NS oil-loaded EVs, the F6 formulation revealed the smallest particle size (278.1 nm), with log-normal size distribution (0.459) and adequate entrapment efficiency. A non-uniform shape was observed in the transmission electron microscopy. The viscosity of F6 formulation hydrogel was 32.34 (Pa·s), which exhibited plastic behavior. In vivo, efficacy studies demonstrated decreased inflammation of the epidermis and dermis and a marked decrease in the levels of IL-17 by NS EV hydrogel compared to plain NS oil and standard drugs (Betamethasone and Dr. JRK Psorolin Oil).ConclusionIt may be concluded from the findings that NS-loaded EV gel was as good as betamethasone cream but more efficacious than the other treatments.
Keywords: micromeritics